NON-EPEC TYPABLE Escherichia Coli Serotypes Causing Urinary Tract Infections at a University Community Clinic, Nairobi, Kenya - J.M KIMANDO; P.O OKEMO (International Journal of Pharma and Bio Sciences, 2010)
Escherichia coli is the predominant cause of urinary tract infections, and is gaining prominence in medical practice due to increasing resistance to widely used antimicrobials including some specified in the world Health Organization’s Model List of Essential Drugs. A cross-sectional analytical research design was conducted to determine the serotypes and antimicrobial resistance phenotypes of Escherichia coli isolated from patients with symptomatic urinary infections. Results obtained show that among the typable enteropathogenic Escherichia coli, serotype 4 was predominant. Over 85 percent of the isolates were sensitive to ceftazidime, ciprofloxacine, gentamicin, norfloxacine and nitrofurantoin. More than 82 percent of the isolates were resistant to cotrimoxazole and ampicillin, 58.69 percent resistant to augmentin and 31.52 percent resistant to nalidixic acid. The drugs ampicillin and cotrimoxazole exhibited minimum inhibitory concentration >2000µg/ml. Most strains were multi drug resistant, and 93 percent of the isolates carried plasmids of molecular weight range 1.8 to 98 MDa.